(untitled) (Birmingham, U.K., 2001)
This book aims to give the reader enough information to be able to use XML from within the .NET Framework in the most efficient manner possible. It will explain in detail the usage of all the XML-related .NET Framework library classes for the manipulation, validation, transformation, and serialization of XML data, using both C# and Visual Basic .NET. It also looks at how the developer can utilize the full power of XML within the .NET Framework, for example, with the new XML capabilities of ADO.NET and ASP.NET. As is demonstrated, the .NET Framework itself uses XML, in configuration files, meta data, and C#'s XML code documentation mechanism, for example. This book is aimed at intermediate-level programmers who have started on their journey towards .NET development, and who want to see how to use XML within their applications to its best advantage. Basic knowledge of C# or Visual Basic .NET, XML, and XML related technologies (XSLT, XPath, and XML Schemas) is necessary.
Keywords: XML (ngôn ngữ đánh dấu văn bản),XML (Document markup language)